Un rite catholique dans un quartier pauvre d’Alger, en 1923 : la communion de Jacques Cormery dans Le Premier Homme d’Albert Camus - Spiquel, Agnès (Romanica Silesiana)
In his autobiographical novel, which was left incomplete due to the author’s accidental death, Camus relates how Jacques Cormery, the protagonist, “receives his First Communion” in order to comply with the demand of his grandmother who wants this matter to be settled before he enters grammar school. It is a purely sociological rite in Jacques’s family. Though empty of meaning, and consequently negative for the child, this step is for him an opportunity to come in contact with mystery. This, however, does not develop in the direction of an intimation of transcendency but towards a deepening understanding of the quotidian mystery that his mother represents, and the obscure bond which unites him to her. Consequently, Camus thus explores the “horizontal transcendency” through which he attempts to elaborate on both his agnosticism and his sense of the sacred. Key words: Albert Camus, autobiographical novel, sacredness/the sacred, agnosticism